Co-integration, error correction, and the econometric analysis of non-stationary data - Banerjee, Anindya (New York ; Oxford : Oxford University Press, 1993)
Considering the econometric analysis of both stationary and non-stationary processes, which may be linked by equilibrium relationships, this text provides a wide-ranging account of the main tools, techniques, models, concepts, and distributions involved in the modelling of integrated processes.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Econometric models